AN ANALYSIS ON TRANSLATION OF METAPHORS IN A NOVEL ENTITLED FALLEN - KADIWANU, VALENTINE TYSHA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: translation, metaphors, metaphor translation procedure, Fallen The existence of many diverse languages results in the closure of information exchange. Translation then appears as the solution, which is not an easy job. Having linguistics skill and knowledge of the culture cannot guarantee the translator to face no problem at all. Metaphor is one of the significant translation problems since it is usually influenced by the culture. Thus, the translator has to carefully consider how to translate metaphor. This study analyzes metaphor translation in a novel entitled Fallen. There are two problems to be solved in the study namely: (1) what kinds of procedure are applied in translating the metaphors; (2) what are the possible reasons in using particular procedure in translat ing the metaphors in Lauren Kate’s novel ent it led Fallen.This study uses qualitative approach in document analysis since it focuses on analyzing and identifying procedures in translating metaphors. The data source are the English and Indonesian version of a novel entitled Fallen, both the English and Indonesian versions. The data are analyzed by using theory about metaphor translation proposed by Newmark (1988).This study reveals that there are five of seven procedures applied to translate the metaphors namely reproducing the same image in the TL (20 data), replacing SL image with a standard TL image (6 data), translating metaphor by simile (11 data), converting the metaphor into sense (13 data), and deleting the metaphor (2 data). There are various possible reasons to use particular procedure namely because the SL images are universal images, the SL images have broad definition or quality, the SL images are confusing, the SL images are offensive, and the SL images are religious terms.The writer suggests the next researchers to use another type of text or using another theory, or to conduct study about metaphor translation in terms of equivalency, accuracy, and appropriateness.